2004
DOI: 10.1016/j.phr.2004.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Traumatic Brain Injury, West Virginia, 1989–1998

Abstract: SYNOPSISObjective. The objective of this study was to describe fatal cases of traumatic brain injury (TBI) among West Virginia residents.Methods. The authors analyzed data from the National Center for Health Statistics Multiple Cause of Death tapes for the period 1989-1998. They compared West Virginia's annualized average TBI death rate with the rates of other states and with the rate among U.S. residents for the same period. U.S. Bureau of Census population estimates were used as denominators.Results. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…These conditions are the reason why the CFR was higher in less populated areas, and why hospital mortality was lower in cases who lived closer to a hospital admitting TBI cases. A comparable finding was published in a study from the United States [ 6 ]: the CFR tended to decrease with an increase in population density (with the notable exception of the District of Columbia).…”
Section: Discussionsupporting
confidence: 85%
“…These conditions are the reason why the CFR was higher in less populated areas, and why hospital mortality was lower in cases who lived closer to a hospital admitting TBI cases. A comparable finding was published in a study from the United States [ 6 ]: the CFR tended to decrease with an increase in population density (with the notable exception of the District of Columbia).…”
Section: Discussionsupporting
confidence: 85%
“…Our findings suggest that systematic differences in care and/or treatment could be contributing to increased mortality in children sustaining TBIs in rural locations. Currently, longer transport times are thought to be associated with the increased risk of injury mortality in rural areas (Adekoya and Majumder 2004 ; Tiesman et al 2007 ). Studies have reported decreased chances of survival with transportation times from injury scene to initial care over 30 min (Grossman et al 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the few TBI studies that include pediatric populations in the US, injury severity has consistently been reported to be higher in rural compared to urban locations (Reid et al 2001 ; Gabella et al 1997 ; Chapital et al 2007 ). In contrast, studies examining urban/rural differences in pediatric TBI mortality have reported mixed results (Gabella et al 1997 ; Chapital et al 2007 ; Adekoya and Majumder 2004 ). Compared to children in metropolitan locations, children in rural areas had a higher frequency of motor vehicle related mechanisms of injury, which are known to be associated with increased injury severity compared to other mechanisms, potentially helping explain severity and mortality differences across regions (Reid et al 2001 ; Gabella et al 1997 ; Chapital et al 2007 ; Thurman et al 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…This may cause differences in the admitted population since TBI related to falls are milder than road traffic related accidents. Except for the UK, assault‐ and violence‐related injuries do not constitute a problem in Europe yet, differently from the USA (Adekoya, 2004). European data on mortality are lower than published data for the US (30/10 5 /year) (Kraus et al., 1984) and much lower than data from South Africa (81/10 5 /year) (Nell and Brown 1991) and Colombia (120/10 5 /year) (Gutierrez et al., 2000).…”
Section: Discussionmentioning
confidence: 99%